Searching for higher-performance, income-generating assets: a mutual fund assessment on asset-backed securities. Issue 6 (5th April 2022) - Li, Wenhui; Loviscek, Anthony; Ortiz-Eggenberg, Miki
Abstract : Purpose: In the search for alternative income-generating assets, the paper addresses the following question, one that the literature has yet to answer: what is a reasonable allocation, if any, to asset-backed securities within a 60–40% stock-bond balanced portfolio of mutual funds? Design/methodology/approach: The authors apply the Black–Litterman model of Modern Portfolio Theory to test the efficacy of adding asset-backed securities to the classic 60–40% stock-bond portfolio of mutual funds. The authors use out-of-sample tests of one, three, five, and ten years to determine a reasonable asset allocation. The data are monthly and range from January 2000 through September 2021. Findings: The statistical evidence indicates a modest reward-risk added value from the addition of asset-backed securities, as measured by the Sharpe "reward-to-variability" ratio, in holding periods of three, five, and ten years. Based on the findings, the authors conclude that a reasonable asset allocation for income-seeking, risk-averse investors who follow the classic 60%–40% stock-bond allocation is 8%–10%. Research limitations/implications: The findings apply to a stock-bond balanced portfolio of mutual funds. Other fund combinations could produce different results. Practical implications: Investors and money managers can use the findings to improve portfolio performance. Originality/value: For investors seeking higher income-generating securities in the current record-low interest rate environment, the authors determine a reasonable asset allocation range on asset-backed securities. This study is the first to provide such direction to these investors.